2018
DOI: 10.1371/journal.pone.0207262
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of commercial mouthwashes on several virulence traits of Candida albicans, viridans streptococci and Enterococcus faecalis colonizing the oral cavity

Abstract: Oral microbiota consists of hundreds of different species of bacteria, fungi, protozoa and archaea, important for oral health. Oral mycoses, mostly affecting mucosae, are mainly caused by the opportunistic pathogen Candida albicans. They become relevant in denture-wearers elderly people, in diabetic patients, and in immunocompromised individuals. Differently, bacteria are responsible for other pathologies, such as dental caries, gingivitis and periodontitis, which affect even immune-competent individuals. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 52 publications
(65 reference statements)
2
38
0
1
Order By: Relevance
“…Many studies on oral microorganisms have reported that CHX is the best mouthwash [14,15], deeming it the gold standard in the chemical treatment against SM and dental caries [1]. Consistent with the present study, other authors showed that CHX-containing mouthwashes (0.2% and 0.06% concentrates) and Total Care Listerine Zero inhibited the formation of plaque by different species of Streptococci [16]. They also reported that CHX-containing mouthwashes were more effective than Total Care Listerine Zero mouthwash.…”
Section: Discussionsupporting
confidence: 90%
“…Many studies on oral microorganisms have reported that CHX is the best mouthwash [14,15], deeming it the gold standard in the chemical treatment against SM and dental caries [1]. Consistent with the present study, other authors showed that CHX-containing mouthwashes (0.2% and 0.06% concentrates) and Total Care Listerine Zero inhibited the formation of plaque by different species of Streptococci [16]. They also reported that CHX-containing mouthwashes were more effective than Total Care Listerine Zero mouthwash.…”
Section: Discussionsupporting
confidence: 90%
“…Povidone iodine (PV-I, 0.23∼1%), cetylpyridinium chloride (CPC, 0.05∼0.10%), and hydrogen peroxide (0.5∼1.5%) all effectively reduce the number of oral microbiota ( Ardizzoni et al, 2018 ; Eggers et al, 2018 ; Li and Meng, 2020 ). Studies have also shown that SARS-CoV, MERS-CoV, and influenza virus A (H1N1) can be efficiently inactivated by these compounds within 1 min ( Kariwa et al, 2006 ; Eggers et al, 2015 , 2018 ; Kampf et al, 2020 ; Li and Meng, 2020 ).…”
Section: Oral Care Interventions For Patientsmentioning
confidence: 99%
“…In what concerns mouthwashes, Ardizzoni et al [132] evaluated the antimicrobial activity of alcohol-free commercial mouthwashes with chlorhexidine digluconate (CHX), fluoride, essential oils, cetylpyridinium chloride (CC), and triclosan. Candida albicans and a cluster of viridans streptococci (frequently present in the oral cavity) were isolated from pharyngeal swabs and tested.…”
Section: Oral Disease Managementmentioning
confidence: 99%
“…Additionally, they were effective in damaging biofilm formation by viridans streptococci that cooperate with the cariogenic S. mutans, and ineffective against viridans streptococci that are natural competitors of S. mutans. On the contrary, in a mixed biofilm, the mouthwashes eradicated S. salivarius but failed to impair C. albicans' biofilm forming ability [132]. Likewise, Tan et al [133] showed that the combination activity of curcumin and 2-aminobenzimidazole against single-and mixed-species biofilms of C. albicans and S. aureus was curiously most potent on mixed biofilms.…”
Section: Oral Disease Managementmentioning
confidence: 99%